RESEARCH ON PROPOSING A COMPREHENSIVE SUPPORT ECOSYSTEM MODEL FOR CHILDREN WITH DISABILITIES AND THEIR FAMILIES IN VIETNAM (Proceedings of International Conference on Special Education, 2025)
Children with disabilities and their families in Vietnam face numerous challenges in accessing education, healthcare, government policies, social integration, and psychological support. This paper analyzes the current situation and proposes solutions to improve the comprehensive support ecosystem for children with disabilities and their families, including five key elements: family, school, community, government policies, and support services. The study employs a sociological survey method involving 215 parents of children with disabilities in 05 provinces/cities in Vietnam (Hanoi capital, Vinh Phuc, Hai Duong, Quang Ninh, Nghe An). Based on the survey results, the research will highlight the realities of how parents' economic impact, knowledge, care, and education skills affect the quality of intervention for children with disabilities. In addition, the research also aims to further observe and assess the barriers in accessing inclusive education and support services for children and their families during the intervention, care, and education process. From this reality, the paper proposes solutions to raise awareness, knowledge, and skills for parents; train specialized teachers; develop inclusive education programs; disseminate and raise community awareness; improve policies and laws; and expand and enhance the quality of support services. The research results are expected to contribute to providing an overview of the support ecosystem for children with disabilities in Vietnam, thereby proposing solutions to improve this ecosystem, creating conditions for children with disabilities to fully develop and integrate into the community.